2011
DOI: 10.2135/cropsci2011.03.0116
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Analysis for the Effect of Rht‐B1 Dwarfing Gene on Coleoptile Length and Seedling Root Length and Number of Bread Wheat

Abstract: It has been documenfed fhaf the dwarfing genes, Rht-Blb and Rht-Dlb, can reduce wheat {Triticum aestivum L.) coleoptile length (CL), buf their effects on number of roofs (RN) and roof length (RL) have nof been determined. Our objectives were to identify quanfitative trait loci (QTL) controlling CL, RN, and RL and to determine if any of fhe QTL correspond to wfieat dwarfing genes. A population consisting of 159 recombinanf inbred lines (RILs) was derived from tbe cross of Rio Blanco {Rht-Blb, Rht-Dla), a semidw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…Singh et al (2016) found that the common bunt HPR QTL co-localized with other beneficial traits including height and rust resistance. The three IDO444-derived QTL have no pleiotropic effect on other traits, such as coleoptile and root length (Li et al 2011), stripe rust (Chen et al 2012), grain yield, heading data, or height (Zhang et al 2014) previously mapped in this population.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Singh et al (2016) found that the common bunt HPR QTL co-localized with other beneficial traits including height and rust resistance. The three IDO444-derived QTL have no pleiotropic effect on other traits, such as coleoptile and root length (Li et al 2011), stripe rust (Chen et al 2012), grain yield, heading data, or height (Zhang et al 2014) previously mapped in this population.…”
Section: Discussionmentioning
confidence: 95%
“…However, it has poor pan bread quality (Windes et al 1995). IDO444 had longer coleoptiles (Li et al 2011) and greater grain yield than Rio Blanco in rain-fed conditions (Zhang et al 2014). …”
Section: Methodsmentioning
confidence: 99%
“…The materials used in this study were selected from a mapping population comprised of 159 F 8:9 recombinant inbred lines (RILs) from a cross IDO444 x Rio Blanco (Li et al, 2011;Chen et al, 2012;Zhang et al, 2014). "IDO444" (no known dwarfing alleles, PI578278) is a tall winter wheat line with improved disease resistance and grain yield (Windes et al, 1995;Zhang et al, 2014), while "Rio Blanco" (Rht4+Rht-B1b, PI531244) is a semi-dwarf hard white winter wheat cultivar released by Agripro Biosciences Inc., Shawnee Mission, KS and widely used in wheat breeding programs (Wu and Carver, 1999;Martin et al, 2001;Carver et al, 2003;Haley et al, 2003;Zhang et al, 2014).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The RhtB1b allele induces insensitiveness to gibberellic acid, thus preventing stem elongation (Peng et al 1999;Hedden 2003). In addition to the reduced height of the plant, the Rht-B1b allele has well-known pleiotropic effects on plant growth, and morphological and physiological characters (Gale and Youssefian 1985;Li et al 2011;Rebetzke et al 2012). It increases yield, mostly under favourable conditions, by altering the proportion of dry matter allocated to grain (De Vita et al 2007;Royo et al 2007Royo et al , 2008Álvaro et al 2008a).…”
Section: Introductionmentioning
confidence: 99%